The drama of public communication in Paraná: the RTVE’s case - Carvalho, Guilherme (2015)
In this case study of RTVE-PR (Rádio e TV Educativa do Paraná), quantitative data on the programming of the educational broadcaster were collected. A reduction in production capacity of the TV was noted as well as an increase of relay content from other stations, such as TV Cultura, which is occupying 29% of the RTVE program schedule. Qualitative aspects of programming were observed, not the technical issues, but the content, where it was identified that a breach of the basic principle of editorial independence of journalism in news programs existed, characterized by the absence of a plurality of opinions and a strengthening of the official sources of information; for example, the governor was one of the most requested.